Islamic Financial Literacy Influence on Generation Z E-Commerce Impulsive Buying - Rahmat Hidayat; Naufal Siantria (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
This study examines the influence of Islamic financial literacy on impulsive buying behavior among Generation Z in the province of West Sulawesi, Indonesia, within the context of e-commerce consumption. The increasing use of digital payment systems and persuasive online marketing strategies has encouraged spontaneous purchasing tendencies, which may conflict with Islamic principles of responsible financial behavior. The purpose of this research is to assess whether the dimensions of Islamic financial literacy knowledge, attitude, and skills can reduce impulsive buying tendencies. A quantitative explanatory method was employed, and data were collected through an online questionnaire distributed to 100 respondents aged 18–25 who actively make purchases on e-commerce platforms. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings indicate that all dimensions of Islamic financial literacy significantly influence impulsive buying behavior; however, the effect is positive, indicating that higher literacy does not necessarily reduce impulsiveness. These results highlight a knowledge behavior gap and underscore the need for behavioral-based Islamic financial education. Keywords: Islamic financial literacy; impulsive buying; Generation Z; e-commerce; SEM-PLS